Abundant resources compensate for the uneven distribution of ungulates in desert grassland - Gou, Xiaowei; Tsunekawa, Atsushi; Tsubo, Mitsuru; Peng, Fei; Cheng, Yunxiang (Frontiers in Plant Science, 2024)
Strategically managing livestock grazing in arid regions optimizes land use and reduces the damage caused by overgrazing. Controlled grazing preserves the grassland ecosystem and fosters sustainability despite resource limitations. Uneven resource distribution can lead to diverse grazing patterns and land degradation, particularly in undulating terrains. In this study, we developed a herbivore foraging algorithm based on a resource selection function model to analyze foraging distribution patterns, predict the probability of foraging, and identify the determinants of foraging probability in cattle in a complex desert landscape encompassing dunes and interdunes. Our findings revealed that cattle prefer areas with abundant vegetation in proximity to water sources and avoid higher elevations. However, abundant resource availability mitigated these impacts and enhanced the role of water points, particularly during late grazing periods. In summary, available resources primarily determine foraging distribution patterns and also lessen the effects of landforms and water distance on patch foraging.. Further, thoughtful water source placement and the subdivision of pastures into areas with varied terrain are crucial considerations.